Ideophonic aspects of some Nyanja drum names - Nurse, G. T. (International Library of African Music, 1968)
The Nyanja language is quite rich in ideophones. It has been calculated that they comprise about nine per cent of the total vocabulary. Ideophones still play an important part in everyday speech; they give to Nyanja much of its charactertistic flavour and provide a fair indication of the value-judgments of the people who speak it. Few languages can as vividly and incidentally convey the quality of a pain, or the changing surface texture of a trodden path. The consistency of food or wood, the speed and direction of movement, and varieties of light and shade, can be expressed with precision and economy. Considering the extent to which a preliterate culture is aural, it is not surprising that so many ideophones have reference to audible phenomena, and that it is possible by using them to differentiate so minutely between sounds. What is more difficult to explain is the comparative paucity of ideophones which apply specifically to music.
Keywords: Chewa (African people); Nyanja (African people); Drum; Nyanja language; Musical instruments; Drum music; Ideophone; Zambia; African Music; Drum (Instrument)